Identifying Perceived Barriers and Benefits to Reducing Energy Consumption in an Affordable Housing Complex. (September 2016) - Reaves, Dan; Clevenger, Caroline M.; Nobe, MaryEllen; Aloise-Young, Patricia A.
Reduction of energy consumption in the affordable housing sector is highly impacted by human behavior. However, only limited behavior change research exists that is aimed at reducing energy consumption in this sector. This study seeks to implement the first two phases of the community-based social marketing (CBSM) framework in an affordable housing setting. The goals of the research are to identify the optimal behaviors for energy reduction and to identify the perceived barriers and benefits associated with those behaviors in a low-income housing facility. The results of this study identify five target behaviors along with their barriers and benefits. In addition, the study identifies potential issues and nuances in the CBSM process that researchers should take into consideration during future implementations of CBSM in affordable housing environments.